2014
DOI: 10.3810/hp.2014.12.1157
|View full text |Cite
|
Sign up to set email alerts
|

30-Day-or-Sooner Readmissions of Gastrointestinal Medical Oncology Patients Following Cancer Center Inpatient Service Discharge: Characteristics and Preventability

Abstract: Readmissions in this cancer population are common and reflect the refractory nature of these diseases and the high disease burdens. The vast majority of readmissions in this population, by our criteria, were not preventable. Our ongoing research in this vulnerable population includes efforts to better characterize and communicate care options, especially in the cases in which there was disagreement between the care team and patient/family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In three studies senior residents performed the review supervised by a senior physicians [19, 26, 59]. In five studies no information on expertise was reported [40, 49, 52, 56, 60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In three studies senior residents performed the review supervised by a senior physicians [19, 26, 59]. In five studies no information on expertise was reported [40, 49, 52, 56, 60].…”
Section: Resultsmentioning
confidence: 99%
“…Agreement and consensus regarding the preventability was handled differently: a double review of each readmission was performed meaning that both reviewers assessed the preventability of the readmissions and came to a mutual agreement [14, 16, 18, 19, 22, 23, 2931, 35, 42, 44, 46, 47, 50, 52, 53, 57]. In some cases a team or panel was consulted when mutual agreement on the preventability was not achieved [5, 48, 55, 60]. Two studies could not be allocated to one of these review categories because the review process was not clearly described or because they used a mix of different methods [39, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing literature on preventability of 30-day readmissions suggests that preventable readmissions are rare events, between 8–20% [ 22 24 ], and as low as 1% for the most vulnerable patients facing refractory malignancies [ 25 ]. Preventability also appears to decrease within the 30-day window [ 26 , 27 ], leading experts to propose that 3 or 7-day readmissions may be a more appropriate accountability measure for hospitals [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 As the validity of the readmission metric continues to be debated among different stakeholders, various cancer viders have investigated their own data to understand the nature of readmissions within their institutions. [8][9][10] Several studies have focused on the postsurgical period, which uses readmission outcomes as a quality measure. [11][12][13][14] Predictors of readmission have been investigated as well (eg, patient characteristics and some regional and hospital effects), although there is a lack of consistency across studies.…”
Section: Introductionmentioning
confidence: 99%